Vitamin C partially prevents reproductive damage in adult male rats exposed to rosuvastatin during prepuberty - Leite, Gabriel Adan Araújo [UNESP]; Figueiredo, Thamiris Moreira [UNESP]; Pacheco, Tainá Louise [UNESP]; Sanabria, Marciana [UNESP]; Silva, Patrícia Villela e [UNESP]; Fernandes, Fábio Henrique [UNESP]; Kempinas, Wilma De Grava [UNESP] (Elsevier, 2017)
Pediatric obesity is closely associated with dyslipidemias and environmental factors, such as diet and lack of physical exercises, which may alter lipid profile in children. Rosuvastatin decreases serum total cholesterol and triglycerides concentrations. Vitamin C (ascorbic acid) plays an important role on sperm integrity and fertility. Juvenile male rats were distributed into six experimental groups that received saline solution 0.9%, 3 or 10 mg/kg/day of rosuvastatin, 150 mg/day of ascorbic acid, or 3 or 10 mg/kg/day of rosuvastatin co-administered with 150 mg/day of ascorbic acid from PND23 until PND53 and then the rats were maintained until sexual maturity. Rosuvastatin-exposed groups showed lower sperm quality, androgen depletion and germ cell death. Ascorbic acid was capable to prevent partially the reproductive adverse effects provoked by rosuvastatin. In conclusion, prepubertal exposure to rosuvastatin provokes long-term reproductive damages at sexual maturity and ascorbic acid supplementation at prepuberty may be a preventive mode against these reproductive adverse effects.
Keywords: Ascorbic acid; Male reproduction; Rosuvastatin; Toxicology